Towards a high-skilled, low-waged workforce? A review of global trends in education, employment and the labour market - Brown, P; Ashton, D; Lauder, H; Tholen, G (ESRC Centre on Skills, Knowledge and Organisational Performance (SKOPE), 2008)
This monograph examines the claim that national economic competitiveness, social justice and individual prosperity, depend on developing a high-skill, high-wage workforce. Based on an analysis of global trends in education, employment and the labour market, we challenge the policy focus on upgrading the skills of the workforce, as it will fail to meet its policy objectives. Without a broader industrial strategy, high skills are a declining source of competitive advantage, given the exponential increase in the global supply of 'knowledge' workers. Equally, the assumption that it would take decades for emerging economies to compete for high-end manufacturing and services, including research and development, have been rapidly undermined. Global competition is now based on quality and price, transforming the relationship between education, jobs and rewards. While we identify a need for further detailed analysis of these issues, there is enough evidence to suggest that the human capital assumption on which government policy rests is no longer 'fit for purpose'.